Prototype of a device adaptable to walk-sticks with a system to communicate the visible spectrum to blind people. - Diaz-Pabón , Sebastián; Murcia-Orozco, Sebastián; Pimiento Serrano, Juan Diego; Torres-Ramírez, Carlos Andrés; Sarmiento Ramos, Jose Luis; Martinez Reyes, Diana (I+ T+ C- Research, Technology and Science, 2023)
This project aims to design and build a device adaptable to canes for blind people that allows them to know the color of everyday objects through a tactile response. The prototype of the device identifies the colors by means of the TCS3200 color sensor that, when detecting the light reflected by the objects, converts it into an electrical signal to later process it with the Arduino Nano microcontroller and thus generate a tactile response using a servomotor. For this purpose, mechanical and electronic designs of the color recognition and representation systems using the Feelipa color code were developed, and a functional prototype of the adaptive device that identifies primary colors was developed. Algorithms for the classification of secondary colors from their RGB values continue to be developed, and the mechanical designs are being improved to take into account aesthetic and ergonomic aspects that facilitate their use